Pengembangan Game Edukasi Materi Barisan Aritmetika dalam Pembelajaran Berdiferensiasi - Rawal, Muhammad; Farman, Farman (Jurnal PEKA (Pendidikan Matematika), 2025)
This study aims to obtain a valid, practical and effective educational game on arithmetic sequence material in differentiated learning. This research is a type of development research that aims to produce a product in the form of an educational game. The development of educational games is carried out through ADDIE steps consisting of analysis, design, development, implementation and evaluation. The subjects of the trial in this study were students of Class X.G of SMA Negeri 2 Kendari in 2024. The data collection instruments in this study consisted of a validation sheet used to determine the validity of the educational game, the performance of game level completion was used to obtain practicality information and learning outcome tests to determine the effectiveness of the educational game. The results of the study showed that (1) overall educational games were in the criteria of very valid and feasible to use, (2) the results of the performance analysis of the use of educational games showed that 100% of students presented with the help of educational games reaching easy, medium, or difficult levels, which means that the learning process was good and included in the practical category, (3) Based on the summative assessment, the results of the percentage of success in realizing the target level of educational games were 76.47%, which was included in the effective category. Thus, educational games are valid, practical and effective for use in differentiated learning.